Soil pH and Liming Issues Affecting Bahiagrass Pasture - Maria Silveira; Joao Vendramini; John E. Rechcigl; Martin B. Adjei (EDIS)
SS-AGR-29, a 5-page illustrated fact sheet by M. Silveira, J. Vendramini, J. E. Rechcigl, and M. B. Adjei, discusses the relationships of soil acidity, nitrogen fertilizer, nutrient availability, and mole cricket-induced bahiagrass decline, and the results of a field study at Range Cattle REC in Ona, which evaluated the long term combined effect of liming and N fertilization on the performance of two bahiagrass pastures. Includes a summary and recommendations for grazing conditions in south-central Florida flatwoods. Published by the UF Department of Agronomy, May 2007.